Perovskite photovoltaic cell preparation method based on flash evaporation process and photovoltaic cell
Perovskite photovoltaic cells were prepared through flash evaporation, which solved the problems of low repeatability and poor stability of perovskite solar cells in practical applications, achieved high efficiency level matching and interface optimization, and improved perovskite photovoltaic cells performance and stability.
Patent Information
- Application Number
- CN202411245726.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-17
AI Technical Summary
In actual production applications, perovskite solar cells have problems such as low repeatability, poor stability, uneven perovskite film formation, poor interface contact and difficulty in preparing large-area films of high-performance battery cells.
Perovskite photovoltaic cell preparation method based on flash evaporation process includes transparent conductive glass pretreatment, electron transport layer deposition, perovskite active layer deposition and evaporation anode, through composite modification of the electron transport layer and pertitanium The process of ore active layer is optimized to achieve energy level matching and interface improvement, and to inhibit ion diffusion and non-radiative recombination.
Improve the performance of perovskite photovoltaic cells, achieve high efficiency level matching, interface optimization, stability and repeatability, solve the problems of low photoelectric conversion efficiency and difficulty in preparing thin films in large areas, and prepare perovskite photovoltaic cells. Excellent performance and high stability.
Smart Images

Figure CN119156102A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite photovoltaic devices and perovskite solar cells, and in particular to a flash evaporation process-based perovskite photovoltaic cell preparation method and a photovoltaic cell. Background Art
[0002] Solar cells are devices that convert solar energy directly into electrical energy through the photovoltaic effect. Solar cells have the advantages of being safe, reliable, noise-free, and pollution-free. At present, the mainstream photovoltaic technology uses silicon-based solar cells, but such cells have high production costs, complex processes, and high energy consumption. In order to solve these significant problems, continuously reduce costs and improve photoelectric conversion efficiency, scientists have proposed the third generation of solar cells, among which the emergence of perovskite solar cells has had a positive impact on the development and application of solar cells.
[0003] This new type of solar cell not only has high energy conversion efficiency and cost-effectiveness, but also reduces dependence on traditional energy, reduces carbon emissions and improves environmental quality.
[0004] Although perovskite cells have excellent device performance, and perovskite materials are low-cost and can be prepared by solution method, there is still a certain gap between perovskite solar cells and actual production applications, such as low repeatability of high-performance battery device efficiency, poor stability, uneven perovskite film formation, poor interface contact, and difficulty in preparing large-area perovskite films. At present, researchers have done a lot of work on interface modification, heat treatment, solvent selection, additives, and structural design in order to obtain perovskite solar cells with better performance and stability.
[0005] Therefore, providing a new preparation process for preparing perovskite solar cells to solve the above-mentioned defects is an urgent problem to be solved. Summary of the invention
[0006] In order to overcome the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a perovskite photovoltaic cell and a photovoltaic cell based on a flash evaporation process. The preparation method of the present invention comprises the following steps: S1. pretreatment of transparent conductive glass; S2. deposition of electron transport layer; S3. deposition of perovskite active layer; S4. sequentially spin coating a hole transport layer on the perovskite active layer, evaporating an anode, and preparing the perovskite photovoltaic cell. The present invention performs a composite modification treatment on the electron transport layer and optimizes the preparation process of the perovskite active layer at the same time, thereby achieving a better energy level matching, passivating interface defects, inhibiting ion diffusion, and reducing non-radiative recombination, and successfully solves the low photoelectric conversion efficiency of perovskite photovoltaic cells due to poor interface contact, and the difficulty of large-area preparation of perovskite thin films; the perovskite photovoltaic cell prepared according to the preparation method of the present invention has the characteristics of excellent performance, high repeatability, and strong stability.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] A method for preparing a perovskite photovoltaic cell based on a flash evaporation process comprises the following steps:
[0009] S1. Transparent conductive glass pretreatment:
[0010] S101. After cleaning the surface of the transparent conductive glass with Triton for 3-5 minutes, rinse with deionized water to remove residual Triton;
[0011] S102. The cleaned transparent conductive glass is ultrasonically cleaned with an isopropanol-acetone mixed solution for 10-15 minutes, then rinsed with deionized water to remove the residual isopropanol-acetone mixed solution, and dried to obtain a pretreated transparent conductive glass;
[0012] S2. Electron transport layer deposition:
[0013] S201. A 200-300 nm thick Nb-doped TiO2 thin film is deposited on the surface of the pretreated transparent conductive glass by a chemical bath deposition method to form a primary electron transport layer;
[0014] S202. A 100-200 nm thick modified SnO2 film is deposited on the surface of the primary electron transport layer by electrospraying to form a secondary electron transport layer;
[0015] S203. The transparent conductive glass deposited with the primary electron transport layer and the secondary electron transport layer is subjected to low temperature annealing treatment at 150-200° C. for 20-30 min;
[0016] S3. Perovskite active layer deposition:
[0017] S301. dissolving the organic-inorganic hybrid perovskite material in an organic solvent to form an organic-inorganic hybrid perovskite solution;
[0018] S302. The organic-inorganic hybrid perovskite solution is evenly spread on the surface of the metal evaporation boat, and is sent into the evaporation chamber together with the transparent conductive glass treated in step S2;
[0019] S303. Evacuate the evaporation chamber until the pressure is lower than 4*10 -3 MPa, irradiate the sample with a heating lamp to raise the temperature of the sample to 50-100℃ and keep it warm for 10-20min;
[0020] S304. By loading a current of 100-200A, the temperature of the metal evaporation boat is raised to 1000-1500°C and maintained for 3-4s, so that the organic-inorganic hybrid perovskite material in the organic-inorganic hybrid perovskite solution is evaporated onto the surface of the secondary electron transport layer to form a 900-1200nm thick perovskite active layer;
[0021] S4. Spin coating a hole transport layer on the perovskite active layer in sequence and evaporating an anode to obtain the perovskite photovoltaic cell.
[0022] Preferably, the transparent conductive glass is one of FTO and ITO.
[0023] Preferably, in step S102, the isopropanol-acetone mixed solution is a mixture of isopropanol and acetone in a mass ratio of 4:1.
[0024] Preferably, in step S201, the chemical bath deposition method specifically includes the following steps:
[0025] S11. Mix 15-30 parts of titanium tetrachloride, 1-4 parts of niobium pentachloride and 2-4 parts of ethanol in parts by mass to obtain a chemical bath;
[0026] S12. immersing the pretreated transparent conductive glass in a chemical bath and reacting at 70-80° C. for 1-3 hours;
[0027] S13. The transparent conductive glass processed in step S12 is placed at 100-150° C. for 20-30 minutes for annealing to form a primary electron transport layer on the surface of the transparent conductive glass.
[0028] Preferably, in step S202, the electrospray method specifically comprises the following steps:
[0029] S21. Mix 10-20 parts of SnCl5·5H2O, 1-5 parts of In2O3, 1-3 parts of graphene, and 50-80 parts of ethanol by mass, and adjust the pH of the solution to 3-4 to form an electrospray stock solution;
[0030] S22. Use a Pelletron tandem accelerator for electrostatic spraying, load the prepared electrospray stock solution into the spray gun, and atomize the solution into tiny droplets through a high voltage electric field;
[0031] S23. applying a negative voltage to the transparent conductive glass treated in step S201, and placing it in the spraying area for electrospraying;
[0032] S24. The transparent conductive glass processed in step S23 is placed at 100-150° C. for 20-30 minutes for annealing to form a secondary electron transport layer on the surface of the primary electron transport layer.
[0033] Preferably, the voltage of the high-voltage electric field is 100-500 kV; the working parameter of the negative voltage is -10 to -50 kV; and the time of the electrospray treatment is 10-20 s.
[0034] Preferably, in step S301, the organic-inorganic hybrid perovskite material is a mixture of PbI2, CH3NH3I, and CH3NH3Br in a mass ratio of 2-3:1-2:1; the organic solvent is a mixture of N-methyl-2-pyrrolidone, dimethyl sulfoxide, methylamine acetate, and semicarbazide in a mass ratio of 2-3:1-2:4-5:1-3; the mass ratio of the organic-inorganic hybrid perovskite material to the organic solvent is 1-3:12-15.
[0035] Preferably, in S4, the hole transport layer is a spiro-OMeTAD film; and the thickness of the hole transport layer is 20-100 nm.
[0036] Preferably, in step S4, the anode is one of a gold electrode and a silver electrode.
[0037] A photovoltaic cell is prepared according to the preparation method.
[0038] Compared with the prior art, the present invention has the following beneficial effects:
[0039] 1. The present invention performs a composite modification treatment on the electron transport layer and optimizes the preparation process of the perovskite active layer, thereby achieving better energy level matching, passivating interface defects, inhibiting ion diffusion, and reducing non-radiative recombination, thereby successfully solving the problems of low photoelectric conversion efficiency of perovskite photovoltaic cells due to poor interface contact and difficulty in large-area preparation of perovskite films;
[0040] 2. The perovskite photovoltaic cell prepared according to the preparation method of the present invention has the characteristics of excellent performance, high repeatability and strong stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 This is a process flow chart of the preparation of the perovskite photovoltaic cell of the present invention;
[0042] Figure 2 The process flow chart of the electron transport layer deposition of the present invention;
[0043] Figure 3 This is a process flow chart of the deposition of the perovskite active layer of the present invention. DETAILED DESCRIPTION
[0044] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] See also Figure 1-3 , the present invention provides a technical solution:
[0046] Example 1
[0047] A method for preparing perovskite photovoltaic cells based on flash evaporation process:
[0048] S1. Transparent conductive glass (FTO) pretreatment:
[0049] S101. After cleaning the surface of the transparent conductive glass with Triton for 3 min, rinse with deionized water to remove residual Triton;
[0050] S102. The cleaned transparent conductive glass is ultrasonically cleaned with an isopropanol-acetone mixed solution for 10 min, then rinsed with deionized water to remove the residual isopropanol-acetone mixed solution, and dried to obtain a pretreated transparent conductive glass;
[0051] S2. Electron transport layer deposition:
[0052] S201. A 200 nm thick Nb-doped TiO2 thin film is deposited on the surface of the pretreated transparent conductive glass by a chemical bath deposition method to form a primary electron transport layer;
[0053] S202. A 100 nm thick modified SnO2 film is deposited on the surface of the primary electron transport layer by electrospraying to form a secondary electron transport layer;
[0054] S203. The transparent conductive glass deposited with the primary electron transport layer and the secondary electron transport layer is subjected to low temperature annealing treatment at 150° C. for 20 min;
[0055] S3. Perovskite active layer deposition:
[0056] S301. Dissolving the organic-inorganic hybrid perovskite material in an organic solvent to form an organic-inorganic hybrid perovskite solution;
[0057] S302. The organic-inorganic hybrid perovskite solution is evenly spread on the surface of the metal evaporation boat, and is sent into the evaporation chamber together with the transparent conductive glass treated in step S2;
[0058] S303. Evacuate the evaporation chamber until the pressure is lower than 4*10 -3 MPa, irradiate the sample with a heating lamp to raise the temperature of the sample to 50°C and keep it warm for 20 min;
[0059] S304. By loading a current of 200A, the temperature of the metal evaporation boat is raised to 1500°C and maintained for 3s, so that the organic-inorganic hybrid perovskite material in the organic-inorganic hybrid perovskite solution is evaporated onto the surface of the secondary electron transport layer to form a 1200nm thick perovskite active layer;
[0060] S4. Spin coating a hole transport layer on the perovskite active layer in sequence and evaporating an anode to obtain the perovskite photovoltaic cell.
[0061] In the above process, the isopropanol-acetone mixed solution is prepared by directly mixing isopropanol and acetone in a mass ratio of 4:1;
[0062] The primary electron transport layer is specifically prepared by the following steps:
[0063] S11. 30 g of titanium tetrachloride, 4 g of niobium pentachloride and 4 g of ethanol were mixed to obtain a chemical bath;
[0064] S12. immersing the pretreated transparent conductive glass in a chemical bath and reacting at 70° C. for 1 h;
[0065] S13. The transparent conductive glass processed in step S12 is placed at 150° C. for 20 min for annealing to form a primary electron transport layer on the surface of the transparent conductive glass;
[0066] The secondary electron transport layer is specifically prepared by the following steps:
[0067] S21. 20 g SnCl5·5H2O, 4 g In2O3, 3 g graphene, and 70 g ethanol were mixed, and the pH of the solution was adjusted to 3 to form an electrospray stock solution;
[0068] S22. Use a Pelletron tandem accelerator for electrostatic spraying, load the prepared electrospray stock solution into the spray gun, set the voltage to 500 kV to form a high voltage electric field to atomize the solution into tiny droplets;
[0069] S23. applying a negative voltage of -10 kV to the transparent conductive glass treated in step S201, and placing it in the spraying area for electrospraying treatment for 10 seconds;
[0070] S24. The transparent conductive glass processed in step S23 is annealed at 150° C. for 20 min to form a secondary electron transport layer on the surface of the primary electron transport layer;
[0071] In step S301, the organic-inorganic hybrid perovskite material includes the following components: 2g PbI2, 2g CH3NH3I, 1g CH3NH3Br;
[0072] The organic solvent comprises the following components: 6 g N-methyl-2-pyrrolidone, 2 g dimethyl sulfoxide, 10 g methylamine acetate, and 2 g thiosemicarbazide;
[0073] The spin coating of the hole transport layer is achieved by the following steps:
[0074] In a water-free and oxygen-free glove box, 30 μl of the prepared 20 mg / mL Spiro-MOeTAD chlorobenzene solution was evenly coated on the perovskite active layer prepared in step S3 using a pipette, and the solution was spin-coated at a speed of 2500 r / min for 20 s to complete the spin coating of the hole transport layer.
[0075] The evaporation anode is achieved by the following steps:
[0076] A gold electrode with a set pattern shape is prepared by vapor deposition on the hole transport layer using a vacuum evaporation method.
[0077] Example 2
[0078] A method for preparing perovskite photovoltaic cells based on flash evaporation process:
[0079] S1. Transparent conductive glass (FTO) pretreatment:
[0080] S101. After cleaning the surface of the transparent conductive glass with Triton for 5 min, rinse with deionized water to remove residual Triton;
[0081] S102. The cleaned transparent conductive glass is ultrasonically cleaned with an isopropanol-acetone mixed solution for 15 minutes, then rinsed with deionized water to remove the residual isopropanol-acetone mixed solution, and dried to obtain a pretreated transparent conductive glass;
[0082] S2. Electron transport layer deposition:
[0083] S201. A 100 nm thick Nb-doped TiO2 thin film is deposited on the surface of the pretreated transparent conductive glass by a chemical bath deposition method to form a primary electron transport layer;
[0084] S202. A 200 nm thick modified SnO2 film is deposited on the surface of the primary electron transport layer by electrospraying to form a secondary electron transport layer;
[0085] S203. The transparent conductive glass deposited with the primary electron transport layer and the secondary electron transport layer is subjected to low temperature annealing treatment at 180° C. for 30 min;
[0086] S3. Perovskite active layer deposition:
[0087] S301. dissolving the organic-inorganic hybrid perovskite material in an organic solvent to form an organic-inorganic hybrid perovskite solution;
[0088] S302. The organic-inorganic hybrid perovskite solution is evenly spread on the surface of the metal evaporation boat, and is sent into the evaporation chamber together with the transparent conductive glass treated in step S2;
[0089] S303. Evacuate the evaporation chamber until the pressure is lower than 4*10 -3 MPa, irradiate the sample with a heating lamp to raise the temperature of the sample to 100°C and keep it warm for 10 min;
[0090] S304. By loading a current of 100A, the temperature of the metal evaporation boat is raised to 1000°C and maintained for 3s, so that the organic-inorganic hybrid perovskite material in the organic-inorganic hybrid perovskite solution is evaporated onto the surface of the secondary electron transport layer to form a 900nm thick perovskite active layer;
[0091] S4. Spin coating a hole transport layer on the perovskite active layer in sequence and evaporating an anode to obtain the perovskite photovoltaic cell.
[0092] In the above process, the isopropanol-acetone mixed solution is prepared by directly mixing isopropanol and acetone in a mass ratio of 4:1;
[0093] The primary electron transport layer is specifically prepared by the following steps:
[0094] S11. 15 g of titanium tetrachloride, 1 g of niobium pentachloride and 2 g of ethanol were mixed to obtain a chemical bath;
[0095] S12. immersing the pretreated transparent conductive glass in a chemical bath and reacting at 70° C. for 1 h;
[0096] S13. placing the transparent conductive glass processed in step S12 at 100° C. for 20 min for annealing to form a primary electron transport layer on the surface of the transparent conductive glass;
[0097] The secondary electron transport layer is specifically prepared by the following steps:
[0098] S21. 10 g SnCl5·5H2O, 1 g In2O3, 1 g graphene, and 50 g ethanol were mixed, and the pH of the solution was adjusted to 3 to form an electrospray stock solution;
[0099] S22. Use a Pelletron tandem accelerator for electrostatic spraying, load the prepared electrospray stock solution into the spray gun, set the voltage to 100 kV to form a high voltage electric field to atomize the solution into tiny droplets;
[0100] S23. applying a negative voltage of -10 kV to the transparent conductive glass treated in step S201, and placing it in the spraying area for electrospraying treatment for 10 seconds;
[0101] S24. The transparent conductive glass processed in step S23 is annealed at 100° C. for 20 min to form a secondary electron transport layer on the surface of the primary electron transport layer;
[0102] In step S301, the organic-inorganic hybrid perovskite material includes the following components: 2g PbI2, 1g CH3NH3I, 1g CH3NH3Br;
[0103] The organic solvent comprises the following components: 4g N-methyl-2-pyrrolidone, 2g dimethyl sulfoxide, 8g methylamine acetate, and 2g thiosemicarbazide;
[0104] The spin coating of the hole transport layer is achieved by the following steps:
[0105] In a water-free and oxygen-free glove box, 30 μl of the prepared 20 mg / mL Spiro-MOeTAD chlorobenzene solution was evenly coated on the perovskite active layer prepared in step S3 using a pipette, and the solution was spin-coated at a speed of 2500 r / min for 20 s to complete the spin coating of the hole transport layer.
[0106] The evaporation anode is achieved by the following steps:
[0107] A gold electrode with a set pattern shape is prepared by vapor deposition on the hole transport layer using a vacuum evaporation method.
[0108] Example 3
[0109] A method for preparing perovskite photovoltaic cells based on flash evaporation process:
[0110] S1. Transparent conductive glass (FTO) pretreatment:
[0111] S101. After cleaning the surface of the transparent conductive glass with Triton for 5 min, rinse with deionized water to remove residual Triton;
[0112] S102. The cleaned transparent conductive glass is ultrasonically cleaned with an isopropanol-acetone mixed solution for 15 minutes, then rinsed with deionized water to remove the residual isopropanol-acetone mixed solution, and dried to obtain a pretreated transparent conductive glass;
[0113] S2. Electron transport layer deposition:
[0114] S201. A 150 nm thick Nb-doped TiO2 thin film is deposited on the surface of the pretreated transparent conductive glass by a chemical bath deposition method to form a primary electron transport layer;
[0115] S202. A 150 nm thick modified SnO2 film is deposited on the surface of the primary electron transport layer by electrospraying to form a secondary electron transport layer;
[0116] S203. The transparent conductive glass deposited with the primary electron transport layer and the secondary electron transport layer is subjected to low temperature annealing treatment at 200° C. for 20 min;
[0117] S3. Perovskite active layer deposition:
[0118] S301. dissolving the organic-inorganic hybrid perovskite material in an organic solvent to form an organic-inorganic hybrid perovskite solution;
[0119] S302. The organic-inorganic hybrid perovskite solution is evenly spread on the surface of the metal evaporation boat, and is sent into the evaporation chamber together with the transparent conductive glass treated in step S2;
[0120] S303. Evacuate the evaporation chamber until the pressure is lower than 4*10 -3 MPa, irradiate the sample with a heating lamp to raise the temperature to 80°C and keep it warm for 10 min;
[0121] S304. By loading a current of 150A, the temperature of the metal evaporation boat is raised to 1300°C and maintained for 3s, so that the organic-inorganic hybrid perovskite material in the organic-inorganic hybrid perovskite solution is evaporated onto the surface of the secondary electron transport layer to form a 1000nm thick perovskite active layer;
[0122] S4. Spin coating a hole transport layer on the perovskite active layer in sequence and evaporating an anode to obtain the perovskite photovoltaic cell.
[0123] In the above process, the isopropanol-acetone mixed solution is prepared by directly mixing isopropanol and acetone in a mass ratio of 4:1;
[0124] The primary electron transport layer is specifically prepared by the following steps:
[0125] S11. 17 g of titanium tetrachloride, 3 g of niobium pentachloride and 4 g of ethanol were mixed to obtain a chemical bath;
[0126] S12. immersing the pretreated transparent conductive glass in a chemical bath and reacting at 80° C. for 1.5 h;
[0127] S13. The transparent conductive glass processed in step S12 is placed at 150° C. for 25 min for annealing to form a primary electron transport layer on the surface of the transparent conductive glass;
[0128] The secondary electron transport layer is specifically prepared by the following steps:
[0129] S21. 17 g SnCl5·5H2O, 3 g In2O3, 3 g graphene, and 68 g ethanol were mixed, and the pH of the solution was adjusted to 3 to form an electrospray stock solution;
[0130] S22. Use a Pelletron tandem accelerator for electrostatic spraying, load the prepared electrospray stock solution into the spray gun, set the voltage to 300 kV to form a high voltage electric field to atomize the solution into tiny droplets;
[0131] S23. applying a negative voltage of -20 kV to the transparent conductive glass treated in step S201, and placing it in the spraying area for electrospraying treatment for 10 seconds;
[0132] S24. The transparent conductive glass processed in step S23 is annealed at 130° C. for 20 min to form a secondary electron transport layer on the surface of the primary electron transport layer;
[0133] In step S301, the organic-inorganic hybrid perovskite material includes the following components: 3g PbI2, 1g CH3NH3I, 1g CH3NH3Br;
[0134] The organic solvent comprises the following components: 6 g N-methyl-2-pyrrolidone, 4 g dimethyl sulfoxide, 8 g methylamine acetate, and 4 g thiosemicarbazide;
[0135] The spin coating of the hole transport layer is achieved by the following steps:
[0136] In a water-free and oxygen-free glove box, 30 μl of the prepared 20 mg / mL Spiro-MOeTAD chlorobenzene solution was evenly coated on the perovskite active layer prepared in step S3 using a pipette, and the solution was spin-coated at a speed of 2500 r / min for 20 s to complete the spin coating of the hole transport layer.
[0137] The evaporation anode is achieved by the following steps:
[0138] A gold electrode with a set pattern shape is prepared by vapor deposition on the hole transport layer using a vacuum evaporation method.
[0139] Example 4: Example 4 is different from Example 1 in the following way. The only difference is that in Example 4, the transparent conductive glass (FTO) in Example 1 is replaced by transparent conductive glass (ITO), and the remaining steps are exactly the same in Example 4 and Example 1.
[0140] Comparative Example
[0141] Comparative Example 1: Comparative Example 1 is different from Example 3 in that step S201 originally existing in Example 3 is omitted in Comparative Example 1, thereby eliminating the preparation of the primary electron transport layer. The remaining steps are exactly the same in Comparative Example 1 and Example 3.
[0142] Comparative Example 2: Comparative Example 2 is different from Example 3 in that step S11 originally existing in Example 3 is omitted in Comparative Example 2, thereby eliminating the use of niobium pentachloride. The remaining steps in Comparative Example 2 and Example 3 are exactly the same.
[0143] Comparative Example 3: Comparative Example 3 differs from Example 3 in that step S202 originally existing in Example 3 is omitted in Comparative Example 3, thereby eliminating the preparation of the secondary electron transport layer. The remaining steps are exactly the same in Comparative Example 3 and Example 3.
[0144] Comparative Example 4: Comparative Example 4 is different from Example 3 in that step S21 originally existing in Example 3 is omitted in Comparative Example 4, thereby eliminating the use of In2O3 and graphene. The remaining steps are exactly the same in Comparative Example 4 and Example 3.
[0145] Comparative Example 5: There are the following differences between Comparative Example 5 and Example 3. The only difference is that in Comparative Example 5, step S303 originally existing in Example 3 is omitted, thereby canceling the step of "irradiating the sample with a heating lamp, heating the sample to 80°C, and keeping it warm for 10 minutes". The remaining steps are exactly the same in Comparative Example 3 and Example 3.
[0146] Performance test: The initial conversion efficiency of the perovskite cells prepared in Examples 1-4 and Comparative Examples 1-5 was tested, and the maximum power point tracking (MPPT) test was performed on the perovskite cells prepared in Examples 1-4 and Comparative Examples 1-5 at the same time, and the working time when the conversion effect dropped to 90% of the initial conversion efficiency was recorded, which was recorded as the optimal working life. The results are as follows:
[0147] Group Conversion efficiency (%) Optimal working life (h) Example 1 22.46 >1800 Example 2 21.78 >1800 Example 3 23.11 >1800 Example 4 23.01 >1800 Comparative Example 1 18.55 >1200 Comparative Example 2 20.71 >1400 Comparative Example 3 18.06 >1200 Comparative Example 4 19.99 >1300 Comparative Example 5 20.65 >1800
[0148] Referring to the above content, it can be seen that the photoelectric conversion efficiency of Examples 1-4 is greater than 21%, the best can reach 23.11%, and the optimal working life is greater than 1800h, which proves that the perovskite photovoltaic cell prepared by the present invention has excellent performance, high repeatability, strong stability, and can be used for a long time; at the same time, compared with Example 3, the photoelectric conversion efficiency and the optimal working life of Comparative Examples 1 and 3 are reduced to varying degrees. The reason is that the lack of the composite electron transport layer increases the charge recombination at the interface, enhances the reverse electron transfer ability, and reduces the forward electron mobility, which reduces the overall conductivity and electron extraction ability of the electron transport layer, and ultimately leads to a decrease in the photoelectric conversion efficiency. The reason why the photoelectric conversion efficiency and the optimal working life of Comparative Examples 2 and 4 decrease to varying degrees compared with Example 3 is that the use of niobium pentachloride / In2O3 and graphene is cancelled, the holes and defect states on the surface of the primary electron transport layer / secondary electron transport layer are difficult to be passivated, and the unpassivated defect states will capture photogenerated carriers to induce non-radiative recombination, thereby reducing the energy level matching between the electron transport layer as a whole and the perovskite, resulting in a decrease in the photoelectric conversion efficiency; the photoelectric conversion efficiency of Comparative Example 5 is reduced compared with Example 3, which proves that the present invention improves the crystallization effect and conversion efficiency of perovskite through the pre-heating treatment step before the flash evaporation process.
[0149] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a perovskite photovoltaic cell based on a flash evaporation process, characterized in that: The following steps are involved: S1. Transparent conductive glass pretreatment: S101. After cleaning the surface of the transparent conductive glass with Triton for 3-5 minutes, rinse with deionized water to remove residual Triton; S102. The cleaned transparent conductive glass is ultrasonically cleaned with an isopropanol-acetone mixed solution for 10-15 minutes, then rinsed with deionized water to remove the residual isopropanol-acetone mixed solution, and dried to obtain a pretreated transparent conductive glass; S2. Electron transport layer deposition: S201. A 200-300 nm thick Nb-doped TiO2 thin film is deposited on the surface of the pretreated transparent conductive glass by a chemical bath deposition method to form a primary electron transport layer; S202. A 100-200 nm thick modified SnO2 film is deposited on the surface of the primary electron transport layer by electrospraying to form a secondary electron transport layer; S203. The transparent conductive glass deposited with the primary electron transport layer and the secondary electron transport layer is subjected to low temperature annealing treatment at 150-200° C. for 20-30 min; S3. Perovskite active layer deposition: S301. Dissolving the organic-inorganic hybrid perovskite material in an organic solvent to form an organic-inorganic hybrid perovskite solution; S302. The organic-inorganic hybrid perovskite solution is evenly spread on the surface of the metal evaporation boat, and is sent into the evaporation chamber together with the transparent conductive glass treated in step S2; S303. Evacuate the evaporation chamber until the pressure is lower than 4*10 -3 MPa, irradiate the sample with a heating lamp to raise the temperature of the sample to 50-100℃ and keep it warm for 10-20min; S304. By loading a current of 100-200A, the temperature of the metal evaporation boat is raised to 1000-1500°C and maintained for 3-4s, so that the organic-inorganic hybrid perovskite material in the organic-inorganic hybrid perovskite solution is evaporated onto the surface of the secondary electron transport layer to form a 900-1200nm thick perovskite active layer; S4. Spin coating a hole transport layer on the perovskite active layer in sequence and evaporating an anode to obtain the perovskite photovoltaic cell.
2. The method for preparing a perovskite photovoltaic cell based on a flash evaporation process according to claim 1, characterized in that: The transparent conductive glass is one of FTO and ITO.
3. The method for preparing a perovskite photovoltaic cell based on a flash evaporation process according to claim 1, characterized in that: In step S102, the isopropanol-acetone mixed solution is a mixture of isopropanol and acetone in a mass ratio of 4:
1.
4. The method for preparing a perovskite photovoltaic cell based on a flash evaporation process according to claim 1, characterized in that: In step S201, the chemical bath deposition method specifically includes the following steps: S11. Mix 15-30 parts of titanium tetrachloride, 1-4 parts of niobium pentachloride and 2-4 parts of ethanol in parts by mass to obtain a chemical bath; S12. immersing the pretreated transparent conductive glass in a chemical bath and reacting at 70-80° C. for 1-3 hours; S13. The transparent conductive glass processed in step S12 is placed at 100-150° C. for 20-30 minutes for annealing to form a primary electron transport layer on the surface of the transparent conductive glass.
5. The method for preparing a perovskite photovoltaic cell based on a flash evaporation process according to claim 1, characterized in that: In step S202, the electrospray method specifically includes the following steps: S21. Mix 10-20 parts of SnCl5·5H2O, 1-5 parts of In2O3, 1-3 parts of graphene, and 50-80 parts of ethanol by mass, and adjust the pH of the solution to 3-4 to form an electrospray stock solution; S22. Use a Pelletron tandem accelerator for electrostatic spraying, load the prepared electrospray stock solution into the spray gun, and atomize the solution into tiny droplets through a high voltage electric field; S23. applying a negative voltage to the transparent conductive glass treated in step S201, and placing it in the spraying area for electrospraying; S24. The transparent conductive glass processed in step S23 is placed at 100-150° C. for 20-30 minutes for annealing to form a secondary electron transport layer on the surface of the primary electron transport layer.
6. The method for preparing a perovskite photovoltaic cell based on a flash evaporation process according to claim 5, characterized in that: The voltage of the high-voltage electric field is 100-500 kV; the working parameter of the negative voltage is -10 to -50 kV; and the time of the electrospray treatment is 10-20 s.
7. The method for preparing a perovskite photovoltaic cell based on a flash evaporation process according to claim 1, characterized in that: In step S301, the organic-inorganic hybrid perovskite material is a mixture of PbI2, CH3NH3I, and CH3NH3Br in a mass ratio of 2-3:1-2:1; the organic solvent is a mixture of N-methyl-2-pyrrolidone, dimethyl sulfoxide, methylamine acetate, and semicarbazide in a mass ratio of 2-3:1-2:4-5:1-3; the mass ratio of the organic-inorganic hybrid perovskite material to the organic solvent is 1-3:12-15.
8. The method for preparing a perovskite photovoltaic cell based on a flash evaporation process according to claim 1, characterized in that: In S4, the hole transport layer is a spiro-OMeTAD film; and the thickness of the hole transport layer is 20-100 nm.
9. The method for preparing a perovskite photovoltaic cell based on a flash evaporation process according to claim 1, characterized in that: In step S4, the anode is one of a gold electrode and a silver electrode.
10. A photovoltaic cell, characterized in that: Prepared according to any one of claims 1 to 9.
Citation Information
Cited By
Process for obtaining perovskite ceramic nanoparticles, photovoltaic cell and method for protecting the photovoltaic cell
WO2026213671A1
